An Analysis of Indonesian Economic Performance Based on Net Export Values from 2015 to 2020 - Zainuddin, Zainuddin; Mufadhdhal, Muhammad Farras (Universitas Serambi Mekkah, 2020)
This study aimed to find out the economic performance of Indonesia based on the net export values measured annually by the Indonesian Central Statistics Agency. The data collected from the agency to be used for this study were the total monthly export and import values of Indonesia from 2015 to September 2020. A descriptive qualitative approach was used for data analysis. The results showed that Indonesia had the poorest economic performance in 2018 and 2019 because the export values in these two years were much lower than the import values. Good economic performances of Indonesia was found in 2015, 2016, 2017, and 2020 (January to September) because the export values during these years were greater than the import values. The best performance was in 2020 with the highest net export value of all. Thus, in the last six years, it can be said that the Indonesian economic performance was not excellent, but it was still fairly good.Â Keywords: Net Exports, Exports, Imports, and Economic Performance